Rumah tradisional Joglo dalam estetika tradisi Jawa - Subiyantoro, Slamet (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2011)
Javanese traditional houses have their own aesthetic values that represent the manifestation of the Javanese way of life in response to the environment. Joglo, as a building, is a symbolic representation of reality whose values exceed its physical form and structure. In the Javanese cultural context, Joglo signifies the establishment of communication with God, both vertically and horizontally, as well as with nature and the surrounding environment.